FACTORS INFLUENCING THE SUSTAINABILITY OF COMPETITIVE ADVANTAGE OF THE EASTERN-EUROPEAN AUTO SECTOR - Lucian-Ovidiu CINADE (Management Intercultural, 2015)

(untitled)
Car-building industry territorial reconfiguration in Europe is the result of several rounds of company delocations from origin countries to emergent countries. Such rounds have been limited by the gradual opening of the national countries, as well as by changes in East European ideology and politics. Hence, about the end of the 90’s, European car-building industry shows considerable disparity, East to West. In the car-building companies’ vision, East-European car-building development potential is basically sustained by both the car low penetration rate, and the low labor cost. On the long term run, gradual valorizing of the East-european trading, with increasing labor costs, may read as a wearing thin of the competitive advantage in car-building industries, as well as problem issues of novel territory attractiveness needing permanent boosting. Country-to-country comparative analysis indicates that competitive advantage of car-building has not gone down in all of the West-European States. Competitive advantage of the West-European car-building industry increases, which can be explained, in part, by adequate strategies, as both labor costs, and cars penetration rate, go up.